Structure-Semantic Analysis Of Warning Road Signs In English (The Peerian Journal, 2025)
This study examines the structure and semantics of some warning road signs in English. The research aims to analyze the linguistic and visual components that contribute to the effectiveness of these signs. The study employs a structural and semantic approach to investigate how these signs convey warnings and influence driver behavior. Findings suggest that a combination of symbolic, lexical, and syntactic elements ensures the clarity and universality of warning road signs.